Analisis Penerimaan Aplikasi Kubuku oleh Pengguna di UPT Perpustakaan Universitas Andalas: Studi Deskriptif dengan Model Technology Acceptance Model (TAM) - Triska, Yona; Erlianti, Gustina (ARZUSIN, 2024)
One form of digital library owned by the Andalas University Library UPT is the Kubuku application, however the use of the Kubuku application in this agency is not optimal. This research aims to analyze the acceptance of the Kubuku application by users at the Andalas University Library UPT. The type of research used is a quantitative approach with descriptive methods. The data collection technique was carried out by distributing questionnaires to the respondents. The total population in this study was 437 people. Samples were taken from 81 users using the Slovin formula with a precision of 10%. The analysis was carried out using the Technological Acceptance Model (TAM) theory which consists of 4 indicators. From each indicator, it was found that users had a perception of the usefulness of the application with a percentage of 74.6% in the good category. Users have a perception of ease of use of the application with a percentage of 84% in the very good category. Users have a good interest in using the Kubuku application with a percentage of 72.6%. And the actual use of the Kubuku application is also categorized as good with a percentage of 64%. Based on the overall results of the research, it can be concluded that there is acceptance of the Kubuku application by users at the Andalas University Library UPT with a percentage of 73.8% which is in the good category.